The Development Ofdevelopment of An Interactive Learning Media in the Indonesian History Subjects X Grade At Smk N 4 Pariaman an Interactive Learning Media in the Indonesian History Subjects X Grade at SMK N 4 Pariaman - Fitria Susilowati; Helmi Hasan (International Journal of Educational Dynamics, 2019)
Learning Media is one of the important components in learning. The importance of using media in learning is to help students understand the history materials. The learning media used in Indonesian History learning is less diverse and less innovative. The lack of optimal use of instructional media in the teaching and learning process makes students difficult understand the contents of the subject matter. The objectives achieved in developing this learning media are to produce interactive learning media on the valid, practical and effective study of the Indonesian History Subject of X Grade. This type of research was a developmental research. This research used a 4-D model consisting of 4 stages: define, design, develop, and disseminate. The validity tests were carried out by experts through a validation assessment sheet. The practical tests were carried out by the teachers and the students through the response sheet. The effectiveness was seen from the learning outcomes through three aspects: cognitive, affective and pyschomotor. Based on the results of the validity test, the practicality test and the effectiveness test obtained an interactive learning media that was valid, practical, and effective. It can be concluded that the interactive learning media developed can be used in studying the Indonesian History Subject of X Grade at SMK Negeri 4 Pariaman.